Ruthless consistency how committed leaders execute strategy, implement change, and build organizations that win - Michael Canic (New York, NY Mcgraw-Hill, 2021)
"When all is said and done, a lot more gets said than done. What is the antidote to this? Ruthless Consistency. According to Harvard Business Review, "most studies still show a 60-70% failure rate for organizational change projects-a statistic that has stayed constant from the 1970s to the present." Drawing on his 20+ years of experience as a strategy and execution consultant specializing in midsize companies, Michael Canic helps committed leaders drive the odds in their favor. In Ruthless Consistency, he identifies the three surprising reasons most strategic change initiatives fail: Leaders unwittingly send mixed messages that demotivate their people and undermine those initiatives. Leaders focus on what they do instead of what their people experience. Leaders are not as committed as they think they are or need to be. The book then introduces an intuitive yet comprehensive model for success. Simply put, leaders who develop the right focus, create the right environment, and build the right team-consistently-are leaders whose organizations win. Finally, it details each element of the model and offers ready-to-apply processes, practices, techniques, and tools to make it happen. It's a must-read for every leader who wants to implement change successfully"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Organizational change